Sociopragmatic Analysis Of Commissive Utterances Used In The Fault In Our Stars - Arga Kurniawan, Kancah Mandra Ac; , Dra. Siti Zuhriah Ariatmi, M. Hum (2016)
Commissive utterance is one of the classifications of illocutionary speech act. In the commissive utterance, the speaker commits to himself to do some future action. This study analyzes the commissive utterances used by the characters in the movie entitled "The Fault in Our Stars". The aims of this study are (1) to find out the types of commissive utterances used in "The Fault in Our Stars" movie, (2) to find out the types of implicatures of commissive utterances, (3) and to find out the violation maxim of commissive utterances. The type of this study is descriptive qualitative method since this study analyzes the data in the form of words. The data source of this study is taken from the movie entitled "The Fault in Our Stars". This study applies documentation by studying deeply on the movie's script. The data are analyzed by using several kinds of theory; types of commissive utterances are analyzed by referring to Searle's commissive utterance classification while the implicature and violating maxim are analyzed by referring to Grice theory. According to Searle's theory there are six categories of commissive utterances, i.e. promise, refuse, guarantee, threat, offer, and volunteer. The researcher found 20 data of mmissiveuterrances. Those are 6 promise 30%, 6 guarantee 30%, 2 refusal 10%, 2 threat 10%, 3 offer 15% and the last is 1 volunteer 5%. The majority of the types of commissive utterances used by the characters in the movie entitled "The Fault in Our Starts" are guarantee and promise. The researcher found 8 of 20 data which revealed implicature, there 5 data contain particularized conversational implicature and 3 data contain generalized conversational implicature. In the violation maxim, the researcher found 5 of 20 data which violated the maxim, 2 data violated the maxim of quantity, 1 data violated the maxim of quality, 1 data violated the maxim of manner, and 1 data violated the maxim of relation.